WAWASAN MANAJEMEN STRATEGIK DALAM PRAKTEK BISNIS BANK SYARl'AH - MUHAMMAD MUHAMMAD (Al Qalam, 2012)
The change of environment frequently demands the carefulness in work of the management in order to be able to recognize the signs of change occurring and its orientation as well as its impacts to the future of the dynamics and the development of bussiness organization. Moreover, the change of environment, especially the external environment, is frequently complex and drastic so that it, directly or indirectly, influences on the stabilily of the business of a company. Indeed, the existing change of environment often play a threat function than an opportunily function. Two main purposes of this article are to formulate the insider's perspective in understanding of the shari'a business actor toward strategic management and to know the map of strategic management in implementing the business of shari'a banking. Key Words: Strategic Management, Shari'a Banking Bussiness.